Beyond retail stores: Managing product proliferation along the supply chain - Isık Biçer; Florian Lücker; Tamer Boyacı (European School of Management and Technology (ESMT), 2020)
Product proliferation occurs in supply chains to produce diverse products from a limited variety of raw materials. In such a setting, manufacturers can establish market responsiveness and/or cost efficiency in alternative ways. Delaying the point of the proliferation helps manufacturers improve the responsiveness by postponing the ordering decisions of the final products until partial or full resolution of demand uncertainty. This strategy can be implemented in two different approaches: (1) redesigning the operations such that the point of proliferation is swapped with a downstream operation and (2) reducing the lead times. To establish cost efficiency, manufacturers can systematically reduce the costs of all operations or postpone the high-cost operations. We consider a multi-echelon and multi-product newsvendor problem with demand forecast evolution to analyze the value of each operational lever of the responsiveness and the efficiency. We use the multiplicative martingale model of forecast evolution to characterize the demand-updating process, and develop a dynamic optimization model to determine the optimal order quantities at different echelons. We show that reducing the lead time of a downstream operation is more beneficial to manufacturers than reducing the lead time of an upstream operation by the same amount, whereas reducing the costs of upstream operations is more favorable than reducing the costs of downstream operations. We also indicate that delaying the proliferation may cause a loss of profit even if it can be achieved with no additional cost. We develop a decision typology that shows effective operational strategies depending on product/market characteristics and process flexibility.
urn:nbn:de:101:1-2020021113491256101164
Keywords: 650; product proliferation; lead-time reduction; process redesign; delayed differentiation